Physicochemistry, Nutritional, and Therapeutic Potential of Ficus carica – A Promising Nutraceutical - Fazel MF; Abu IF; Mohamad MHN; Mat Daud NA; Hasan AN; Aboo Bakkar Z; Md Khir MAN; Juliana N; Das S; Mohd Razali MR; Zainal Baharin NH; Ismail AA (Dove Medical Press, 2024)
Muhammad Fattah Fazel,1,2 Izuddin Fahmy Abu,1 Mohamad Haiqal Nizar Mohamad,3 Noor Arniwati Mat Daud,1 Ahmad Najib Hasan,1 Zainie Aboo Bakkar,1 Muhammad Alif Naim Md Khir,4 Norsham Juliana,5 Srijit Das,6 Muhamad Razin Mohd Razali,1 Nurul Hana Zainal Baharin,2 Arashidatul Akmar Ismail2 1Institute of Medical Science Technology, Universiti Kuala Lumpur, Kuala Lumpur, Malaysia; 2Faculty of Pharmacy and Biomedical Sciences, MAHSA University, Jenjarom, Selangor, Malaysia; 3Malaysian Institute of Chemical and Bioengineering Technology, Universiti Kuala Lumpur, Alor Gajah, Malacca, Malaysia; 4Tropical Infectious Diseases Research and Education Centre (TIDREC), University of Malaya, Kuala Lumpur, Malaysia; 5Faculty of Medicine and Health Sciences, Universiti Sains Islam Malaysia, Nilai, Negeri Sembilan, Malaysia; 6Department of Human and Clinical Anatomy, College of Medicine and Health Sciences, Sultan Qaboos University, Muscat, OmanCorrespondence: Izuddin Fahmy Abu, Institute of Medical Science Technology, Universiti Kuala Lumpur, Jalan Sultan Ismail, Kuala Lumpur, 50250, Malaysia, Email izuddin@unikl.edu.myAbstract: In an era where synthetic supplements have raised concerns regarding their effects on human health, Ficus carica has emerged as a natural alternative rich in polyphenolic compounds with potent therapeutic properties. Various studies on F. carica focusing on the analysis and validation of its pharmacological and nutritional properties are emerging. This paper summarizes present data and information on the phytochemical, nutritional values, therapeutic potential, as well as the toxicity profile of F. carica. An extensive search was conducted from various databases, including PubMed, ScienceDirect, Scopus, and Google Scholar. A total of 126 studies and articles related to F. carica that were published between 1999 and 2023 were included in this review. Remarkably, F. carica exhibits a diverse array of advantageous effects, including, but not limited to, antioxidant, anti-neurodegenerative, antimicrobial, antiviral, anti-inflammatory, anti-arthritic, antiepileptic, anticonvulsant, anti-hyperlipidemic, anti-angiogenic, antidiabetic, anti-cancer, and antimutagenic properties. Among the highlights include that antioxidants from F. carica were demonstrated to inhibit cholinesterase, potentially protecting neurons in Alzheimer's disease and other neurodegenerative conditions. The antimicrobial activities of F. carica were attributed to its high flavonoids and terpenoids content, while its virucidal action through the inhibition of DNA and RNA replication was postulated due to its triterpenes content. Inflammatory and arthritic conditions may also benefit from its anti-inflammatory and anti-arthritic properties through the modulation of various signalling proteins. Studies have also shown that F. carica extracts were generally safe and exhibit low toxicity profile, although more research in this aspect is required, specifically its effects on the skin. In conclusion, this study highlights the potential of F. carica as a valuable natural therapeutic agent and dietary supplement. However, continued exploration on F. carica's safety and efficacy is still required prior to embarking on clinical trials, as its role in personalized nutrition and medication will open a new paradigm to improve health outcomes.Keywords: antioxidant, dietary supplement, fig, natural compound, phytochemical